Antibiosis of proteins and metabolites of three species of Trichoderma against paraguayan isolates of Macrophomina phaseolina - Cubilla-Ríos, Alberto Anastacio (2019)
Introduction. Macrophomina phaseolina is a necrotrophic fungus that is difficult to control. Biocontrol agents, like the species of the genus Trichoderma, are an alternative for the management of crop diseases caused by this plant-pathogen. Objective. The objective of the present work was to determine the antibiosis capacity of Trichoderma arundinaceum, T. brevicompactum and T. harzianum, against two isolates of M. phaseolina. Materials and methods. Experiments were carried out from October 2015 to March 2016. Three reference strains of Trichoderma were used: T. arundinaceum (IBT40837), T. brevicompactum (IBT40841) and T. harzianum T34 (CECT2413); and two isolates of M. phaseolina (FCQ6 and FCQ9). Direct confrontation and antibiosis assays were performed, and profiling of proteins and metabolites secreted from Trichoderma. Results.The Trichoderma species significantly inhibited the growth of both M. phaseolina isolates in the direct confrontation assay, cellophane and/or dialysis membrane. In the direct confrontation trial, the greatest inhibition of fungal growth was observed at 96 h. M. phaseolina isolated from sesame (Sesamum indicum L. cultivar Escoba blanca) allowed the evaluation of the antifungal activity of the molecules of high and low molecular weight even up to 120 h. T. arundinaceum maintained 100% growth inhibition in both cellophane and dialysis membrane indicating that low molecular weight metabolites were enough for complete growth inhibition of this M. phaseolina isolate. In contrast, T. brevicompactum and T. harzianum demonstrated the importance of high molecular weight molecules for the maintenance of antifungal activity. In addition, the complexity of secondary metabolites and proteins secreted by the three Trichoderma species was demonstrated. Conclusion. This work is the first description of the antifungal activity of T. arundinaceum and T. brevicompactum against M. phaseolina and also highlights the potential of fungi isolated from native soil as a biological alternative for the control of plant-pathogenic fungi of agricultural importance.